Hemangioblastomatosis-associated negative-pressure hydrocephalus managed with improvised shunt. (December 2018) - Badran, Abdul; Shepard, Matthew J.; Ksendzovsky, Alexander; Murayi, Roger; Hayes, Christina; Smart, DeeDee; Chittiboina, Prashant
Highlights: Negative-pressure hydrocephalus is associated with subarachnoid hemorrhage. Subarachnoid hemorrhage is a rare complication of extramedullary hemangioblastomas. Increased brain compliance is likely responsible for low-pressure hydrocephalus. Negative-pressure hydrocephalus may be managed with a simple improvised shunt. Abstract: Low-pressure hydrocephalus (LPH) is a rare clinical diagnosis, characterized by neurologic decline and ventriculomegaly that persists despite normal to low intracranial pressure. LPH is typically managed by negative-pressure drainage via ventriculostomy, followed by low-resistance shunt insertion. We present the case of a middle-aged man with a history of hemangioblastomatosis who had spontaneous subarachnoid hemorrhage. He was treated with a ventriculoperitoneal shunt and then underwent resection of a Meckel's cave hemangioblastoma and whole brain irradiation. One month later, he presented to us with worsening symptoms and hydrocephalus despite shunt interrogations and revisions revealing no malfunction. Ventriculostomy drainage at negative-pressure was required for resolution of symptoms and ventriculomegaly, leading us to a diagnosis of LPH. This was successfully treated using an improvised ultra-low pressure valveless ventriculoperitoneal shunt, with maintained resolution of LPH for over one year. The system was created by ligating the distal slit valve end of a peritoneal catheter to prevent reflux and allow sub-zero pressure drainage by siphoning.